Visit-to-visit Variability of Blood Pressure and Risk of Stroke: Results of the Kailuan Cohort Study - Haijiang Dai (Nature Portfolio, 2017)
Abstract Uncertainty persists regarding the need to address blood pressure (BP) variability in the general population to reduce the heavy burden of stroke. In this cohort study, we prospectively recruited 57,927 participants from southeast of Beijing, who have completed all 3 health examinations between 2006 and 2010. BP variability was defined as the coefficient of variation (CV) across these 3 visits. Over a median follow-up of 3.0 years, we identified 582 first stroke cases. Of these, 489 (84.0%) were ischemic strokes and 94 (16.2%) were hemorrhagic strokes. After multivariable adjustment, the hazard ratios (HR) (95% Confidence Intervals, CI) of comparing participants in the highest versus lowest quartile of CV of systolic blood pressure (SBP) was 1.44 (1.11, 1.87) for any stroke, 1.33 (1.00, 1.77) for ischemic stroke, and 2.17 (1.09, 4.35) for hemorrhagic stroke. Similar results were also observed when the CV of SBP was considered as a continuous exposure variable (per SD increase). Moreover, higher variability of diastolic blood pressure (DBP) was also significantly associated with the risk of any stroke and specifically with hemorrhagic stroke, but not with ischemic stroke. In conclusion, higher visit-to-visit BP variability might be an important target to reduce stroke risk, particularly for hemorrhagic stroke.